Effects of intestinal flora on cerebral hemorrhage area and brain tissue inflammation in acute hemorrhagic stroke: Intestinal flora in acute hemorrhagic stroke - Mu, Xiue; Zhang, Jin; Li, Huili; Li, Hongying; Mu, Zitong; Ye, Fengfang; Li, Jiaxuan; Ye, Fengli (Cellular and Molecular Biology, 2024)
To explore the impacts of intestinal flora on cerebral hemorrhage area and brain tissue inflammation in acute hemorrhagic stroke, seventy-two male C57BL/6 mice were randomly separated into 6 groups (n=12), the experimental group (EG, day 1, day 3 and day 7) and the control group (CG, day 1, day 3 and day 7). The mouse cerebral hemorrhage model was established by collagenase injection, and the EG received 0.4 mL fecal filtrate of healthy mice once a day, and the CG received the same amount of normal saline transplantation. The mNSS score, hematoma volume and cerebral edema content were used to evaluate nerve function injury and brain injury degree at each time point after operation. The expressions of inflammatory factors were detected by western blot. We found that at each time point after operation, compared with the CG, nerve function deficit scores of mice in the EG declined (P<0.05), the water content of mice brain tissue in the EG declined (P<0.05), and the protein expressions of inflammatory factors in the EG were decreased (P<0.05). Relative to the CG, the volume of hematoma in the EG declined on day 3 along with day 7 after operation (P<0.05). In conclusion, intestinal flora can reduce cerebral hemorrhage area and brain tissue inflammation, and then improve the performance of nerve function deficit in acute hemorrhagic stroke.